DEVELOPING AN E-CRM MODEL TAILORED TO MSMES NEEDS FOR ENHANCING COMPETITIVENESS IN THE DIGITAL ERA - Akhmad, Khabib Alia; Nurohman, Nurohman (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy but often face barriers in adopting digital technologies, particularly in customer relationship management (CRM). This study aimed to develop and evaluate a contextually adaptive Electronic Customer Relationship Management (E-CRM) model tailored to MSMEs' operational realities. Using a mixed-methods approach, the research included needs analysis, model development, and pilot implementation involving five MSMEs in Surakarta. Key barriers identified were lack of human resources, high development costs, and low digital literacy. The proposed web-based E-CRM prototype included simplified interfaces, data analytics, and communication automation. Results showed improvements in customer retention (+23%), reduced marketing costs (?18%), and increased revenue (+12%). The findings highlight the model’s potential to enhance MSME competitiveness through accessible, user-friendly digital innovation.